Training student volunteers as community resource navigators to address patients' social needs: A curriculum toolkit - Gautam, Diwas; Sandhu, Sahil; Kutzer, Kate; Blanchard, Lillian; Xu, Jacqueline; Sotelo Munoz, Veronica; Dennis, Erika; Drake, Connor; Crowder, Carolyn; Eisenson, Howard; Prvu Bettger, Janet (Frontiers in Public Health, 2022)
Introduction: Few resources are available to train students to provide patients assistance for obtaining needed community-based services. This toolkit outlines a curriculum to train student volunteers to become “community resource navigators” to serve patients via telephone at partner health sites. Methods: University students co-designed the Help Desk navigator program and training for volunteer navigators as part of an academic-community partnership with a local Federally Qualified Health Center (FQHC). The multi-modal curricula consisted of five components: didactic instruction on social determinants of health and program logistics, mock patient calls and documentation, observation of experienced navigator interaction with patients, supervised calls with real patients, and homework assignments. In 2020, training materials were adapted for virtual delivery due to the COVID-19 pandemic. Trainees completed a survey after completion to provide qualitative feedback on the training and preparedness. Results: The training was offered for the first cohort of 10 student volunteer navigators in 2019, revised and then offered for 13 undergraduate and nursing students over 6 weeks in 2020. In the training evaluation, trainees described the new knowledge and skills gained from the training, the long-term benefits towards their educational and professional career goals, and helpful interactive delivery of the training. Trainees also highlighted areas for improvement, including more time learning about community resources and practicing challenging patient conversations. Conclusions: Our peer-to-peer, multi-modal training prepares student volunteers to become community resource navigators. Student, eager for meaningful clinical experiences, are an untapped resource that can help patients with their social needs. Keywords: social determinants of health; social needs; primary care; volunteer models; training; curriculum; students; academic-community partnership